Understanding the Challenges of the Hilsa Fishing Community in Bangladesh: The River of Life - Hossain, A.B.M. Arman; Mahdi, Gazi Muhammad Abdullah; Pramanik, Md. Mehedi Hasan (Journal of Sustainability and Environmental Management, 2023)
This study examines the economic, livelihood, and social-environmental conditions of the Meghna Riverbank Hilsa fishermen in the Chandpur region of Bangladesh. The research methods encompassed household surveys, surveys conducted during fishing activities, individual interviews, focus group discussions (FGD), key informant interviews (KII), direct observation, and problem analysis with priority ranking. To gather comprehensive information about the socio-economic conditions and livelihood strategies of the Meghna Riverbank hilsa fishermen, a semi-structured interview schedule was conducted. The findings reveal that these fishermen face exploitation, financial instability, and extreme poverty, relying solely on the river for their income. They lack access to fishing equipment and land due to river erosion, and basic necessities such as family planning, health and sanitation facilities, and education are inadequate. The overall situation is further exacerbated by social and economic constraints, including a growing number of fishermen, low incomes, limited alternative sources of income, loan repayment difficulties, piracy, rising prices, and resource disputes among stakeholders. To improve their standard of living, the study recommends effective interventions, cooperation between government and non-government organizations, and meticulous execution of strategies.